Effect of Supplementation with Olive Oil on Some Properties of Bio-Yoghurt - Ammar, El-Tahra M. A; M. M, Ismail; A. K, El-Shazly; M. Z, Eid (The Asia Journal of Applied Microbiology, 2014)
The effect of fortification with olive oil on yoghurt quality was investigated. Control yoghurt was made using classic yoghurt culture and whole milk. Other four yoghurt treatments were made by ABT-5 culture and whole milk fortified with 0, 1, 2, and 4% virgin olive oil. The sixth treatment was prepared using ABT culture and skim milk with 4% virgin olive oil. Changes in rheological, chemical, microbial and organoleptic properties of yoghurt were monitored during refrigerated storage (4°C) of yoghurt for 15 d. Samples of yoghurt with added olive oil to whole milk showed a slight decrease in titratable acidity during the 180 min of fermentation. Adding of olive oil had no clear effect on coagulation time and curd tension whereas decreased the syneresis of yoghurt. Acidity, TS, fat and TVFA contents of yoghurt supplemented with olive oil were higher than those of control whereas the contents of TN and WSN were similar in both. Yoghurt samples fortified with olive oil had less numbers of TVBC. The addition of olive oil improved the viability of lactic acid bacteria and bifidobacteria. The bifidobacteria counts were sufficient to yield numbers of beneficial organisms that were higher than the accepted threshold (106 cfu.g-1) for a probiotic effect. Also, olive oil adding improved the body, texture and flavor of the yoghurt.